Revised web impact factor analysis of Timor Leste University website during COVID-19 pandemic - Tenia Wahyuningrum; Condro Kartiko; Ariq Cahya Wardhana; Teotino Gomes Soares (Bulletin of Electrical Engineering and Informatics, 2021)
The global coronavirus disease 2019 (COVID-19) pandemic requires the Timor Leste government to make a school from home policy. This policy has encouraged several universities to improve the quality of their distance learning services. However, it seems that the government has not gone deep enough to conduct a preliminary study on each university website's readiness to face this. Based on previous research, the university website impact factor is one of the criteria for increasing webometrics rankings. Still, it is not explained in detail the types of referring pages and domains that can affect webometrics rankings. This research investigates the extent to which R-WIF affects webometrics and examines the factors that can improve the university website's quality. We surveyed the revised web impact factor (R-WIF) at seven universities in Timor Leste to determine their academic sites' relative standing. The results show, although some universities have increased the number of backlinks, the webometrics university ranking prefers backlinks that come from high-authorization sites such as .edu and .gov. The correlation value indicates this phenomenon between R-WIF and Webometrics of 0.464, which means moderate. Universities in Timor Leste need to implement several strategies to improve Webometrics rankings, especially visibility.